Enzalutamide in castration‐resistant prostate cancer patients with visceral disease in the liver and/or lung: Outcomes from the randomized controlled phase 3 AFFIRM trial. Issue 2 (20th September 2016) - Loriot, Yohann; Fizazi, Karim; de Bono, Johann S.; Forer, David; Hirmand, Mohammad; Scher, Howard I.
Abstract : BACKGROUND: Patients with metastatic castration‐resistant prostate cancer (mCRPC) and visceral metastases have a worse prognosis than those with nonvisceral metastases. Treatment with the androgen receptor inhibitor enzalutamide in the phase 3 AFFIRM trial led to significant improvements in outcomes for patients with mCRPC. For the current report, the authors analyzed the efficacy of enzalutamide among patients from the AFFIRM trial who had visceral disease. METHODS: Patients who had liver and/or lung metastases at baseline were selected for prespecified overall survival (OS) and exploratory post hoc analyses, including prostate‐specific antigen (PSA) response and the time to PSA and radiographic progression. RESULTS: In patients who had liver metastases (n = 92), enzalutamide was associated with a lower risk of radiographic progression (hazard ratio [HR], 0.645; 95% confidence interval [CI], 0.413‐1.008), improved 12‐month OS (37.7% vs 20.6%) and radiographic progression‐free survival (rPFS) (11.6% vs 3.0%) rates, and higher PSA response rates (35.1% vs 4.8%) compared with placebo. Enzalutamide‐treated patients who had lung metastases (n = 104) had improved median OS (HR, 0.848; 95% CI, 0.510‐1.410), a substantially reduced risk of radiographic progression (HR, 0.386; 95% CI, 0.259‐0.577), improved 12‐month OS (65.1% vs 55.3%) and rPFS (30.9% vs 8.2%) rates, increased time to PSA progression (HR, 0.358; 95% CI, 0.204‐0.627), and a better PSA response rate (52.1% vs 4.9%) compared with those who received placebo. No increase in treatment‐related adverse events was observed for the visceral metastases cohort compared with the nonvisceral metastases cohort. CONCLUSIONS: Across multiple endpoints, patients who have visceral metastases have better outcomes with enzalutamide than with placebo. Cancer 2017;123:253–262. © 2016 American Cancer Society . Abstract : Patients with metastatic, castration‐resistant prostate cancer and visceral metastases, such as liver or lung metastases, have a worse prognosis than those with nonvisceral metastases. Enzalutamide‐treated patients with liver or lung metastases have better outcomes than those who receive placebo.